Characterization of soybean choline kinase cDNAs and their expression in yeast and Escherichia coli. - Monks, D E (1996)
An expressed sequence tag from Arabidopsis that displayed sequence homology to mammalian and yeast choline kinases was used to isolate choline kinase-like cDNAs from soybean (Glycine max L.). Two distinct cDNAs, designated GmCK1 and GmCK2, were recovered that possessed full-length reading frames, each sharing approximately 32% identity at the predicted amino acid level with the rat choline kinase. A third unique choline kinase-like cDNA, GmCK3, was also identified but was not full length. Heterologous expression of GmCK1 in yeast (Saccharomyces cerevisiae) and GmCK2 in both yeast and Escherichia coli demonstrated that each encodes choline kinase activity. In addition to choline, other potential substrates for the choline kinase enzyme include ethanolamine, monomethylethanolamine (MME), and dimethylethanolamine (DME). Both soybean choline kinase isoforms demonstrated negligible ethanolamine kinase activity. Competitive inhibition assays, however, revealed very distinct differences in their responses to DME and MME. DME effectively inhibited only the GmCK2-encoded choline kinase activity. Although MME failed to effectively inhibit either reaction, an unexpected enhancement of choline kinase activity was observed specifically with the GmCK1-encoded enzyme. These results show that choline kinase is encoded by a small, multigene family in soybean comprising two or more distinct isoforms that exhibit both similarities and differences with regard to substrate specificity.